Cost Effective Strategy to Disseminate IPM Technology: A Case of Banke and Surkhet District of Nepal - Khanal, Arjun; Regmi, Punya Prasad; KC, Gopal Bahadur; KC, Dilli Bahadur; Dahal, Kishor Chandra (International Journal of Social Sciences and Management, 2021)
Integrated Pest Management (IPM) is a holistic approach in reducing damage caused by pests without harming the environment. A study on cost effectiveness strategy to disseminate IPM technology was conducted in the Banke and Surkhet districts of Nepal. For assessing the spread of information, farmers were asked a series of questions during the survey to determine knowledge of IPM and degree of IPM adoption. Using descriptive statistics and differences in means, analysis was done on relationships among access to information, IPM knowledge and adoption, and word-of-mouth diffusion of IPM techniques to neighboring farmers. For the evaluation of dissemination methods efficiency and to examine the cost for using the different dissemination methods of IPM technology followed by IPM IL project in Banke and Surkhet district, the cost measurements was focused only on the dissemination methods of IPM technology with a public cost such as mass media, agricultural officers, MPC, collection centre, FFS, CBFs, cooperatives, neighboring farmers, agro-vets and field days. When the number of farmers needing to receive training for one farmer to adopt IPM practices is known, and then that value can be multiplied by the cost per farmer trained which allows in providing the cost per farmer adopting the technology by transfer method. Capacity building in IPM technology development and dissemination in the study area was I/NGOs working in that area. Market Planning Committee of Banke and Surkhet district has played a vital role in disseminating IPM technology in cost effective and efficiently. Int. J. Soc. Sc. Manage. Vol. 8, Issue-1: 272-276